KREATIVITAS MEDIA MENDONGENG PADA MATA KULIAH BAHASA JAWA AUD DI MASA PANDEMI COVID-19 - Hery Setyowati; Khasanah Khasanah (Dharmas Education Journal (DE_Journal), 2021)
Embedding character education should be started early, especially in childhood distinguishing things based on visualization and what is heard (early childhood). One of the ways to instill character is storytelling by prioritizing local culture such as the use of regional languages ​​such as Javanese. This study aims to describe the creativity of Ivet University students in making storytelling media in the Javanese AUD course during the Covid-19 pandemic. The method used is mixed methods between quantitative and qualitative. The target of this research is to focus on making Javanese storytelling media for early childhood (AUD) for PG-PAUD students of Ivet University in the odd semester of 2020/2021 which consists of 30 students. The results of the research on the creativity of storytelling media used by students in storytelling in the Javanese language include multimedia, dolls, pictures, books, and without using other supporting media. This shows as prospective teachers or storytellers, they must have the ability to package fairy tales and optimize their abilities in composing and selecting the right fairy tale media. Storytelling also has attention, affective, cognitive, and compensatory functions for children. Fairytale media that is appropriate and adapted to regional characteristics such as Java can help children enrich vocabulary and imagination so that children's development becomes more optimal.